Cardiorenal protective effects of Tanhuo decoction in acute myocardial infarction via regulating multi-target inflammation and metabolic signaling pathways - Guo, Chenglong; Zhang, Tianxing; He, Lingqian; Zhang, Minyu; Chu, Yanyan; Sun, Xipeng; Han, Xuexue; Liu, Yijiang; Song, Juexian; Xia, Jinggang (Frontiers in Pharmacology, 2025)
IntroductionInflammation is a key driver of adverse outcomes in acute myocardial infarction (AMI), yet current western anti-inflammatory therapies are limited by their single-target nature and side effects. Traditional Chinese medicine (TCM), such as Tanhuo Decoction (THD), offers a multi-target, low-toxicity alternative.MethodsIn a randomized controlled trial, AMI patients with high inflammatory responses received either standard Western medicine (WM) alone or combined with THD for 3 days. Clinical outcomes and inflammatory markers were assessed, and proteomic and network pharmacology analyses were performed.ResultsThe THD + WM group showed significant reductions in neutrophil counts and hs-CRP levels, along with improved creatinine clearance rate (CCR), compared to WM alone. Proteomic analysis revealed downregulation of pro-inflammatory proteins (PTX3, IL-18, TNFRSF11A) and upregulation of the anti-inflammatory IL1RL2. THD also modulated lipid metabolism and insulin sensitivity pathways.DiscussionsTHD enhances the anti-inflammatory and metabolic benefits of standard AMI therapy through multi-target pathway regulation. These findings support its integration into modern cardiovascular care, particularly for patients with high inflammatory and metabolic risk.